Rezension zu "Recht verstehen. Wie Laien, Juristen und Versicherungsagenten die ‚Riester-Rente‘ interpretieren" von Angelika Becker und Wolfgang Klein. Berlin, Akademie Verlag 2008 - Engberg, Jan (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2011)
Review of „Recht verstehen. Wie Laien, Juristen und Versicherungsagenten die ‚Riester-Rente‘ interpretieren“ von Angelika Becker und Wolfgang Klein; Berlin 2008: Akademie Verlag: „In the current literature, there is no lack of general and detailed works dealing with language and comprehension, including in the area of law; there is, however, a dearth of empirical studies dealing with cognitive process analysis. This book fills that gap.“